Penguatan Manfaat Bank Sampah untuk Eliminasi Tempat Perkembangbiakan Nyamuk DBD - Sulistyawati Sulistyawati (LPPM UNIVERSITAS DIAN NUSWANTORO, 2022)
Ngalang Village is one of the cultural tourism villages in Gunungkidul. Along with the village development, the community must adjust to it—including the cleanliness of the environment. In addition to aesthetic reasons, keeping the environment clean will be useful for maintaining public health, such as preventing the breeding of dengue mosquitoes. A waste bank is a community-based waste management method. Until now, Padukuhan Sambeng did not have a waste bank. The technique used is to provide material through leaflets, lectures, and discussions using PowerPoint. The result of this community service is that it is known that the people in Padukuhan Sambeng have a desire to manage waste. This is the background of this community service so that people have knowledge about waste banks and can form waste banks in their environment in the future. However, it is still carried out conventionally due to limited knowledge and is unhealthy.